Decision Making Towards Integration of Sustainability Into Project Management : A Multilevel Theory Building Approach - Daneshpour, Hosein; Takala, Josu (De Gruyter Open, 2017)
In recent years project management has reached into a new paradigm because of integration of sustainability into the projects. The paper argues that multilevel approach is the key driver of successful sustainable project portfolio management. Hereby, this paper strives to underpin the theory and the logic behind the sustainable project management, while providing sustainable competitive advantages. Therefore, it develops an innovative multilevel framework, and analyses the current project management products and processes, and consequently presents a more holistic insight for the implementation of sustainability in project portfolio management.
Keywords: multilevel theory building; front-end eco-efficiency; stochastic frontier analysis; sustainable development; sustainable decision making; fi=Tuotantotalous|en=Industrial Management|